Cellular mosaicism for X-linked polymorphisms and IRAK1 expression presents a distinct phenotype and improves survival following sepsis. Issue 3 (5th November 2013) - Chandra, Rachna; Federici, Stephanie; Németh, Zoltán H; Csóka, Balázs; Thomas, James A; Donnelly, Robert; Spolarics, Zoltán
Abstract : X chromosome cellular mosaicism for IRAK1 expression in mice increases circulating B cell numbers and preconditions for improved sepsis outcome. ABSTRACT: ChrX cellular mosaicism for X-linked genetic polymorphisms in females versus the single ChrX representation in males denotes a genetic difference, which may contribute to gender bias in the inflammatory response. This hypothesis was tested in female F1 offspring of consomic mice (BL6J-ChrX A/J /NaJ) that were homokaryotic or mosaic for the active BL6 and AJ ChrXs or for IRAK1 deficiency linked to the BL6 ChrX. Sepsis was initiated by CLP. IRAK1-deficient and IRAK1-mosaic mice showed similar protection from sepsis-induced mortality and reduced IL-6 and IL-10 release compared with WT. BM cellularity and blood B cell counts were increased in naive IRAK1-mosaic mice compared with WT-mosaic or IRAK1-deficient animals. Sepsis-induced BM cell depletion was greater in IRAK1-mosaic mice compared with WT-mosaic or IRAK1-deficient subjects, whereas splenic B and T cell depletion was less in IRAK1-mosaic and IRAK1-deficient than WT-mosaic mice. Skewing toward AJ or BL6-ChrX-expressing cells was assessed by testing allele-specific expression of strain-variant Xkrx and BTK genes. In naive IRAK1-mosaic mice, BM and blood cells with the active BL6-ChrX, were greater than cells expressing the AJ-ChrX (cell ratio 2.5 in IRAK1-mosaic; 1.5 in WT-mosaic mice). Sepsis decreased cell ratios more in IRAK1-mosaic than in WT-mosaic mice. The study reveals functional variability in cellular mosaicism for IRAK1 expression and natural X-linked polymorphisms during sepsis. Mosaicism for IRAK1 expression is accompanied by skewing toward deficient immune cell populations, producing a phenotype that is preconditioned for improved sepsis outcome similar to that observed in IRAK1 deficiency.